2016
DOI: 10.1136/svn-2016-000021
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal imaging findings in normal-appearing white matter of leucoaraiosis: a review

Abstract: Leucoaraiosis (LA), also referred to as white matter hyperintensities (WMHs), are usually seen as patchy or confluent hyperintense areas on T2-weighted or fluid-attenuated inversion recovery MRI in the elderly. It is often asymptomatic in its early stages, yet its persistent evolution to more advanced stages may lead to substantial neurological dysfunction including dementia, stroke and death. Despite its clinical significance, the pathogenic mechanisms underlying LA development are uncertain. In patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…In future longitudinal studies, we will assess whether WM‐hypo later spread to involve areas that currently only demonstrate WM‐hyper. Though WM‐hyper is nonspecific and associated with many factors, age is consistently the strongest predictor of lesion accumulation in community‐based studies (King, Chen, et al, ; Zhong & Lou, ). We found the expected linear correlation between larger WM‐hyper and WM‐hypo (Figure ) volume with greater age.…”
Section: Discussionmentioning
confidence: 99%
“…In future longitudinal studies, we will assess whether WM‐hypo later spread to involve areas that currently only demonstrate WM‐hyper. Though WM‐hyper is nonspecific and associated with many factors, age is consistently the strongest predictor of lesion accumulation in community‐based studies (King, Chen, et al, ; Zhong & Lou, ). We found the expected linear correlation between larger WM‐hyper and WM‐hypo (Figure ) volume with greater age.…”
Section: Discussionmentioning
confidence: 99%
“…11 Besides, CSVD-related white matter damage is not confined to WMH region but spread widely to normal appearing white matter. 12,13 Thereby, WMH cannot accurately represent white matter damage. Analyzing the white matter in DMVs drainage area with imaging techniques that can reflect microstructural changes would provide more solid evidence for the DMVs disruption-related white matter damage in CSVD.…”
Section: Introductionmentioning
confidence: 99%
“…Normal-appearing white matter refers to the areas around the WMH that appear normal on conventional magnetic resonance images, yet may already display low perfusion or microstructural changes ( Maillard et al, 2011 ; Fu et al, 2014 ; Maillard et al, 2014 ; Pelletier et al, 2015 ; Zhong and Lou, 2016 ). A previous study found a stronger association between the disruption of NAWM integrity and psychomotor dysfunction when compared with WMH load ( Hirsiger et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%